Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Perilaku Keuangan Mahasiswa Pendidikan Ekonomi Universitas Muhammadiyah Bengkulu - Selviani, Ayudho; Sazili, Sazili; Pramudia, Anggun (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The study was montivated by the increasing consumptive lifestyle and low financial literacy among students, which have an impact on unwise financial behavior. The purpose of this study was to determine the effect of financial literacy and lifestyle on the financial behavior of students of the Economic Education Study Program, FKIP, Muhammadiyah University of Bengkulu. The research method used was quantitative research using multiple linear regression analysis techniques. Data collection techniques were observation, questionnaires, and data processing using the IBM SPSS 21 analysis tool. The sampel of this study consisted of 35 students. The results of the study indicate that financial literacy and lifestyle have a significant influence on students’ financial behavior. This was proven through the F law and t test with a significant value below 0.05. Based on the results of the determination test, it was found that the influence of financial literacy and lifestyle variables on financial behavior reached 51.5%. these results indicate the importance of increasing financial understanding and responsible student financial behavior.